If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -5) = -26 Reorder the terms: 2(-5 + 2x) = -26 (-5 * 2 + 2x * 2) = -26 (-10 + 4x) = -26 Solving -10 + 4x = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 4x = -26 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = -26 + 10 4x = -26 + 10 Combine like terms: -26 + 10 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| y^2+27=0 | | 8a+9=9 | | (x+3)(x+7)=0 | | 23=7-8x | | (7r^5+10r^2-2)-(9r^5-8r^2+10)= | | 6+9c=-21 | | 2n+2=-78 | | f(x)=x^2-1 | | 6+9c=21 | | 15(0.30)+0.05x=(x+0.05) | | (x^3/3z)^-3 | | -4(-24+8y)=-64 | | 6-(p/5)=3*q | | 3(4x+2)-4(2x-5)= | | 3(-1x-6)=-48 | | s=180(60-2) | | 4x^9y^7+8x^7y^6+28xy=0 | | 175.00+550.00x*1.00x=35.000+1680.00x | | 10(-5x+13)=-470 | | 6-p/5=3q | | 175.000+55.00x*1.00x=35.000+1680.00x | | 4x-2y=36 | | 64m-16+14-21m= | | (5c^5+4c^2-3)-(8c^5-2c^2+19)= | | 5(5x-8)=-265 | | -4(2x+6)=-24 | | 2+3/4g=32 | | y-7=-8(x-(-11)) | | 2b-0.5=3b | | 175.000+550.00x*1x=35.000+1680.00x | | 6x+1=48 | | 43.00+24.00f=211 |